Special beer consuption in cities of mesoregion South Goiana - Borges, L. C. R.; Perfeiro, D. G. A.; Siqueira, A. P. S. (Scientific Electronic Archives, 2017)
Beer is one of the alcoholic beverage most consumed in Brazil and is related to the generation of income in the country. However, the most consumed beers are currently the type lager and larges in mass production. However, there beers on the market with different processing and more delicate ingredients, special calls. Therefore, the aim of this study was to analyze the consumption of beer in the southern cities of Goiás and understand the place of the special beers that context. For that were used online forms with mandatory and closed questions on socioeconomic aspects of consumers, the consumption of beer and also peculiarities of consumption. It was noted that 78% of beer drinkers were hormens, and that, in general, consumers were young adults and belonged to social classes C and D and that beer consumption habits are higher on weekends and holidays. 50% of consumers said they never consumed craft beer and were higher income. 51% of them said to note the differences between the special beers and mass production, but in general is not easy to find these beers on the market. It was noted at the end that beer is a product that appeals to consumers in the region and the special beer if it were more widespread and accessible could be marketed more frequently.